2008
DOI: 10.1017/s0007114507886338
|View full text |Cite
|
Sign up to set email alerts
|

Dietary soya saponins increase gut permeability and play a key role in the onset of soyabean-induced enteritis in Atlantic salmon (Salmo salar L.)

Abstract: Saponins are naturally occurring amphiphilic molecules and have been associated with many biological activities. The aim of the present study was to investigate whether soya saponins trigger the onset of soyabean-induced enteritis in Atlantic salmon (Salmo salar L.), and to examine if dietary soya saponins increase the epithelial permeability of the distal intestine in Atlantic salmon. Seven experimental diets containing different levels of soya saponins were fed to seawater-adapted Atlantic salmon for 53 d. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
3
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(206 citation statements)
references
References 45 publications
(58 reference statements)
15
174
3
14
Order By: Relevance
“…However, other anti-nutritional factors such as saponins and antigenic compound could be existed (Yang et al, 2010). Saponins in soybean product was reported to affect the fish appetite (Bureau et al, 1998) and it was also reported by Knudsen et al (2007) that soya saponins, in combination with one or several unidentified components in soybean might induce inflammatory reaction in the distal intestine of Atlantic salmon. The presence of such anti-nutritional factors in the higher soybean meal level diets in this present study may lead to the poor appetite of the fish and the enteritis symptoms as observed in marble goby juvenile.…”
Section: Discussionmentioning
confidence: 97%
“…However, other anti-nutritional factors such as saponins and antigenic compound could be existed (Yang et al, 2010). Saponins in soybean product was reported to affect the fish appetite (Bureau et al, 1998) and it was also reported by Knudsen et al (2007) that soya saponins, in combination with one or several unidentified components in soybean might induce inflammatory reaction in the distal intestine of Atlantic salmon. The presence of such anti-nutritional factors in the higher soybean meal level diets in this present study may lead to the poor appetite of the fish and the enteritis symptoms as observed in marble goby juvenile.…”
Section: Discussionmentioning
confidence: 97%
“…Alvarez and Torres-Pinedo (1982) suggested that soybean lectin bound to rabbit jejunal enterocyte apical membranes has a potentiating effect on saponin's detrimental influence on epithelial barrier function. Knudsen et al (2008) recently demonstrated that adding purified saponins from soybeans to a fishmealbased diet did not elicit an inflammatory response in the distal intestine or changes in faecal dry matter, and caused only minor changes in intestinal permeability compared to the same diet without saponins added. Nor did lupin kernel meal from sweet lupins (L. angustifolius) elicit inflammation.…”
Section: Norwegian Scientific Committee For Food Safetymentioning
confidence: 99%
“…Saponins are secondary plant compounds that have been tested in aquafeeds with different results. While some reports documented the toxic effect of saponin in fish and its negative effects to the gut epithelium (Knudsen et al, 2008), some studies concluded saponin promotes growth (Francis et al, 2005). Furthermore, saponin has been studied as a natural steroid to promote sex inversion to an all-male population, which could represent an alternative to the use of androgenic hormones in tilapia culture (Francis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%